Food Safety Awareness, Food Policies, and Gender: A Review and an Empirical Examination from Nepal - Khanal, Aditya Raj; Gurung, Rita Kumari; Timilsina, Ram Hari (Nepal Public Policy Review, 2023)
Hunger and malnutrition are critical challenges for developing countries. Access to sufficient safe and nutritious food is the key factor in addressing food security, health, and nutritional goals. Food safety and security are vital components of sustainable food systems. However, in developing countries like Nepal, food safety issues have received limited attention within the food systems. This study aims to review the relationship between food safety and food security, sustainable food systems, awareness, and food policies in Nepal, while also discussing the potential roles of women in these areas. Furthermore, the empirical examination presents our findings based on primary survey data from 604 consumer households in five major metropolitan areas of Nepal, Particularly focusing on gender differences in food safety awareness and purchase of fresh produce. Our overall findings suggest that the basic food safety practices and the enforcement of regulations have been overlooked in Nepal. Moreover, the study also underscores the potential roles women could play in enhancing awareness of safer fresh produce systems and safer food consumption. However, the findings also indicate that women in Nepal have lower awareness of food safety compared to men, emphasizing the need to improve education and awareness among women. To fully harness the potential of women as effective initiators, implementers, and promoters of enhancing food safety and sustainable food systems, awareness and training programs on food safety should prioritize the participation of women. It is crucial to encourage their involvement in food-related activities, leadership and management, and entrepreneurship.